New enantioselective synthesis of the anticonvulsant drug pregabalin (lyrica) based on a hydrolytic kinetic resolution method - Mujahid, Mohammad; Muthukrishnan, Murugan (Chirality, 2013)
A practical and efficient enantioselective synthesis of the anticonvulsant drug pregabalin is described for the first time using Jacobsen's hydrolytic kinetic resolution of a terminal epoxide as a key step and a source of chirality. Chirality 25:965-969, 2013. (c) 2013 Wiley Periodicals, Inc.
Keywords: anticonvulsant drug; Hydrolytic kinetic resolution; pregabalin